Adopting a knowledge management concept in securing the privacy of electronic medical record systems - Samsuri, Suhaila; Ismail, Zuraini; Ahmad, Rabiah (Springer Berlin Heidelberg, 2013)
As the enhancement of Information Technology (IT) in various management fields escalates, the realization of knowledge management (KM) concept is considered as significant. This concept can be applied in considering information privacy as a component in designing a computerized system. Consequently, this paper proposes the adoption of explicit and tacit knowledge concepts in identifying the privacy of information components in order to construct a secured electronic medical record (EMR) system. A preliminary investigation involving interviews with a selected group of hospital information system (HIS) developers has been conducted earlier on. The findings of this study revealed four important components to be factored in any privacy preservation framework for HIS. They are namely, legislation, ethical, technology and cultural. By applying the KM concept into these four components, it can further derive more systematic guidelines in order to achieve the privacy preservation of information. Nevertheless, further research must be developed as to yield a more inclusive guideline in designing an EMR system that is reliable, specifically in addressing the need of securing patient’s personal medical information privacy.